Designing Decision Support System for Midwifery Students’ Tuition Fees Problem - Chandrawati Putri Wulandari (International Journal of Innovation in Enterprise System, 2021)
Education is an essential need and an important element to create a broad-minded youth. While inIndonesia, the rate of tuition fees is still imbalanced with the economic rate. Thus, many peopledecided to discontinue their higher education. Decision making plays an important role to manageorganizations, including in educational institutions, as one of the main duties in managerial is makingdecisions. This study took place in a midwifery academy in Malang. In response to this situation, theacademy has a policy to alleviate students by paying the tuition fees in instalments. However, manystudents are in arrears as the result of this policy. Thus, management needs to take some considerationbefore making a decision toward the problem. Those considerations require high accuracy and timeconsuming to process information that support decision making. Currently, the decision-makingprocess in this academy is still semi-automated, in which some processes are still done manually,which affect longer time to make decisions, and the accuracy of calculations could not be fullyguaranteed. According to this condition, the purpose of this research is to design a decision supportsystem that enables us to process information for decision making and to offer decision alternativesfor decision makers. This research employs Systems Development Life Cycle (SDLC) with a decisiontable as a method to create decision alternatives. The prototype was developed using Visual StudioC#.Net. The result shows that by using the proposed prototype of DSS, decision makers can reduce5-10 minutes of decision making process compared to the old semi-automated system which stillrequired manual calculation and data collection and analysis before making the decision. A completedata and more detailed parameters for decision criteria are required to implement the proposedprototype of DSS in the institution with more objective consideration in the decision making processas the future work.